Pengaruh Kepercayaan Terhadap Online Repurchase Intention: Intermediary Trust dan Seller Trust - Indani, Farinza Tiara; Andriani, Juwita; Wahyuningsih, Adityas (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
In the e-marketplace, trust consists of two categories, namely trust in intermediaries and trust in sellers. This research aims to empirically examine the influence of these two types of consumer trust on purchasing behavior and determine which one is more dominant in explaining purchasing behavior. The research objectives were achieved by conducting a survey among e-marketplace users in Indonesia who have experience shopping on websites such as TikTok Shop, Tokopedia, Lazada, Shopee, Bukalapak, and similar platforms that facilitate trading without selling their own products. The sample in this study consisted of 31 e-marketplace users in Indonesia. Structural Equation Modeling (SEM) analysis using Smart Partial Least Square (Smart PLS) version 7.0 software was used to test the hypotheses. The results of this study indicate a significant influence of benevolence and integrity on trust in intermediaries, while competence does not have a significant influence on trust in intermediaries. Trust in intermediaries has a significant influence on trust in the seller community, and trust in intermediaries has a significant influence on the intention to repurchase on the e-marketplace. Trust in the seller community does not have a significant influence on the intention to repurchase on the e-marketplace. Trust in intermediaries does not mediate the influence of trust in sellers on the intention to repurchase in the e-marketplace.